1993
DOI: 10.1002/prep.19930180508
|View full text |Cite
|
Sign up to set email alerts
|

Shaped charge jet interaction with Highly Effective Passive Sandwich Systems ‐ experiments and analysis

Abstract: The development and investigation of reactive sandwich targets and their interaction with shaped charge jets is one of the many research areas, where important contributions were made by Manfred Held. Such reactive sandwiches are known to be extremely effective against jets, but have a number of disadvantages. In this work, the interaction of the copper jet from a shaped charge calibre 136 mm with a double sandwich system, each sandwich consisting of a non‐reacting layer between outer steel plates, is investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…According to the literature, materials used in such sandwich arrangement are e.g. steel plates and rubber [15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, materials used in such sandwich arrangement are e.g. steel plates and rubber [15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Thoma. K et al [3] showed that the rubber-based composite armor has the advantage of security, without environment impact and none secondary kill effect. Held.…”
Section: Introductionmentioning
confidence: 99%